Designing EDGE (Enhanced destination growth and engagement) to Improve the performance of marine tourism in East Java - Halik, Abdul; Yasin, Muhammad; Sumiati, Sumiati (Edelweiss Applied Science and Technology, 2024)
Marine tourism has emerged as a significant contributor to the regional economy in East Java, Indonesia. However, the growth of this sector is hindered by inadequate infrastructure, limited community engagement, and underdeveloped marketing strategies. This research presents the EDGE (Enhanced Destination Growth and Engagement) model as a comprehensive solution to enhance the performance of marine tourism destinations in East Java. EDGE is a strategic framework that integrates sustainable destination management, innovation-driven tourism product development, and community-based participation. The study employs a mixed-method approach, incorporating both qualitative and quantitative analyses. Key findings reveal that the implementation of EDGE leads to increased visitor satisfaction, improved local community involvement, and heightened environmental sustainability. Recommendations for policy integration and long-term development are also discussed.